Pendidikan Multikuturalisme dan Pendidikan Agama Islam - batubara, manaon (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2015)
Generally, education is a type of effort which is conducted to foster and develop the human person (student) directly and gradually, because maturity and optimal development and growth of student is taking place through education process. Islamic education is one of effort to educate and Islamic teaching to be way of life of the one. Multicultural society is the community which able to forward various kinds of cultural diversity in the wider environment of society and believe that the diversity is an inevitability that cannot be denied. Therefore, this paradigm is point of view or attempt which can be directing society to find its space of life through various of sub-culture, so that it is not based on an ethnic sentiment, locality, religion, and primordialism rigidly. Teaching the multicultural paradigmâespecially in the Islamic educationâactually is not yet constituted by study and research deeply. Due to in Islamic perspective, that multiculturalism should be studied critically.